Ocular ischemic syndrome with bilateral carotid artery stenosis in a patient with chronic tophaceous gout - Mohammad Razali, Amirah; Mohamed Shafit, Muhammad Adri; Md Saleh, Rafidah; Mohmood, Adzleen; Mohd Isa, Mujammad (Springer Science and Business Media LLC, 2023)
Ocular ischaemic syndrome is a rare, blinding condition which usually presents rather late. This occurs mainly due to stenosis or occlusion of the carotid artery which supplies the ocular structures. Bilateral involvement may occur in 1 in 5 cases but may be asymmetrical. We report a case of bilateral ocular ischaemic syndrome secondary to left common carotid artery total occlusion and severe right proximal internal carotid artery stenosis in a patient who is an active smoker with chronic tophaceous gout. His vision remained stable after a year of follow-up, with the main emphasis of optimizing his medical condition and smoking cessation.